2016
DOI: 10.1007/s00894-015-2895-7
|View full text |Cite
|
Sign up to set email alerts
|

The sphere-in-contact model of carbon materials

Abstract: A sphere-in-contact model is presented that is used to build physical models of carbon materials such as graphite, graphene, carbon nanotubes and fullerene. Unlike other molecular models, these models have correct scale and proportions because the carbon atoms are represented by their atomic radius, in contrast to the more commonly used space-fill models, where carbon atoms are represented by their van der Waals radii. Based on a survey taken among 65 undergraduate chemistry students and 28 PhD/postdoctoral st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…20 Based on the sphere-incontact model this result suggests the formation of covalent bonds between nitrogen and cobalt. 21 However, the electronic structure of Ta 3 N 5 does not have any unpaired electrons on the surface nitrogen, which indicates when cobalt is co-adsorbed, these sites are re-hybridized into states with unpaired electrons, that can then form the covalent Co-N.…”
Section: Effect Of Co Promoters On H 2 Chemisorptionmentioning
confidence: 99%
“…20 Based on the sphere-incontact model this result suggests the formation of covalent bonds between nitrogen and cobalt. 21 However, the electronic structure of Ta 3 N 5 does not have any unpaired electrons on the surface nitrogen, which indicates when cobalt is co-adsorbed, these sites are re-hybridized into states with unpaired electrons, that can then form the covalent Co-N.…”
Section: Effect Of Co Promoters On H 2 Chemisorptionmentioning
confidence: 99%
“…In the following section, we provide evidence that there are two bonding interactions that take place based on the sphere-in-contact model. 65 We have taken literature values for the atomic radius of the elements participating in the bonding and drawn to scale a sphere-in-contact model of the tilt end-on adsorption configuration for N 2 on Co 3 Mo 3 N. This is depicted in Figure 5 From the optimized structures presented in Table 2, we find that the tilt angle ranges between 152 and 158°with an average value at 155°. We have used the sphere-in-contact model to provide an explanation of the bonding in the tilt end-on configuration.…”
Section: Resultsmentioning
confidence: 99%
“…This is a well-defined adsorption configuration with a tilt angle equal to 155° in which the dihedral d (Co–Mo–N–N) of this bond is found to be 0. In the following section, we provide evidence that there are two bonding interactions that take place based on the sphere-in-contact model . We have taken literature values for the atomic radius of the elements participating in the bonding and drawn to scale a sphere-in-contact model of the tilt end-on adsorption configuration for N 2 on Co 3 Mo 3 N. This is depicted in Figure…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the sphere-in-contact model [28], the bond length (BL) between atoms is the sum of their atomic radii (AR):…”
Section: Fitting the Sphere-in-contact Model To Crystallographic Datamentioning
confidence: 99%
“…We have recently shown that there is one more physical molecular model, the sphere-in-contact model. [26] This new model is intermediate between the wire-frame and space-fill models and has the basic advantage that it shows the location of the electron density more accurately. In this paper, we use the sphere-in-contact model design to build the structure of rhombohedral graphite and pinpoint new properties with potential applications through theoretical treatment of the spherein-contact model.…”
Section: Introductionmentioning
confidence: 99%